Faults Geometry and the Role of Fluids in the 2016–2017 Central Italy Seismic Sequence. Issue 14 (29th July 2018) - Chiarabba, C.; De Gori, P.; Cattaneo, M.; Spallarossa, D.; Segou, M.
Abstract: The 2016–2017 Central Italy seismic sequence ruptured overlapping normal faults of the Apennines mountain chain, in nine earthquakes with magnitude Mw > 5 within a few months. Here we investigate the structure of the fault system using an extensive aftershock data set, from joint permanent and temporary seismic networks, and 3‐D Vp and Vp / Vs velocity models. We show that mainshocks nucleated on gently west dipping planes that we interpret as inverted steep ramps inherited from the late Pliocene compression. The two large shocks, the 24 August, Mw = 6.0 Amatrice and the 30 October, Mw = 6.5 Norcia occurred on distinct faults reactivated by high pore pressure at the footwall, as indicated by positive Vp / Vs anomalies. The lateral extent of the overpressurized volume includes the fault patch of the Norcia earthquake. The irregular geometry of normal faults together with the reactivated ramps leads to the kinematic complexity observed during the coseismic ruptures and the spatial distribution of aftershocks. Plain Language Summary: In this study we present refined earthquake locations and tomographic images of the upper crust to investigate the mechanisms of the 2016 Amatrice and Norcia destructive earthquakes. We find that earthquakes ruptured distinct segments of the fault system, partially reutilizing preexisting faults inherited from the previous compressional phase. Overpressurized fluids within the carbonate rocks facilitate the reactivation of faults during the large ruptures. Key Points: The two large shocks of Amatrice and Norcia nucleated on distinct and parallel faults reactivated by high pore pressure in the footwall The irregular geometry of normal faults and reactivated ramps feeds in the complexity observed during coseismic ruptures and aftershocks Rapid definition of overpressurized volumes along the fault system has implications for the a priori identification of nucleation locations